The Effectiveness of Learning to Write Narrative Text Using Problem Based Learning and Discovery Learning Based Learning on Parenting Pattern - Nur Aini, Indah; Zulaeha, Ida; Susilogati Sumarti, Sri (Universitas Negeri Semarang, 2020)
Learning to write narrative text needs to use an effective learning model so that learning becomes easier. Problem-based learning (PBL) and direct learning (DL) are two learning models that both have advantages in practicing writing skills. Besides, the factors of parenting patterns were considered as to have an important role in developing vocabulary which is also important in presenting the narrative. This study aims to analyze the effectiveness of the PBL and DL models in learning to write narrative text, as well as the interaction between the effectiveness of the PBL and DL models with parenting pattern. This type of research was experimental research with a quasi-experimental method. The instrument used to measure the effectiveness of the PBL and DL models is a test (pretest and posttest) and questionnaire instrument was used to classify the parenting styles of students. The data analysis technique used were the t test and ANOVA test. The results of the t-test showed that there was a difference in the average writing skills of students' narrative text with the PBL model and the DL model based on the type of parenting pattern and there was an interaction between the effectiveness of learning to write narrative text using PBL and DL models with parenting pattern. PBL models are effectively used in democratic parenting and permissive parenting pattern, while the DL model is effective for authoritarian parenting pattern. It can be concluded that PBL and DL models are effective for learning to write narrative text for certain parenting pattern.